Impact of Trans-Resveratrol-Sulfates and -Glucuronides on Endothelial Nitric Oxide Synthase Activity, Nitric Oxide Release and Intracellular Reactive Oxygen Species - Angela Ladurner; Daniel Schachner; Katharina Schueller; Marc Pignitter; Elke H. Heiss; Veronika Somoza; Verena M. Dirsch (Molecules, 2014)
Resveratrol (3,5,4'-trihydroxy-trans-stilbene) is a polyphenolic natural product mainly present in grape skin, berries and peanuts. In the vasculature resveratrol is thought to boost endothelial function by increasing endothelial nitric oxide synthase (eNOS) expression, by enhancing eNOS activity, and by reduction of reactive oxygen species (ROS) levels. Recent studies show that dietary resveratrol is metabolized in the liver and intestine into resveratrol-sulfate and -glucuronide derivatives questioning the relevance of multiple reported mechanistic in vitro data on resveratrol. In this study, we compare side by side different physiologically relevant resveratrol metabolites (resveratrol sulfates- and -glucuronides) and their parent compound in their influence on eNOS enzyme activity, endothelial NO release, and intracellular ROS levels. In contrast to resveratrol, none of the tested resveratrol metabolites elevated eNOS enzyme activity and endothelial NO release or affected intracellular ROS levels, leaving the possibility that not tested metabolites are active and able to explain in vivo findings.